Cytotoxicity, Antioxidant, Antibacterial, and Photocatalytic Activities of ZnO–CdS Powders - Irina Zgura (Materials, 2020)
In this work, ZnO−CdS composite powders synthesized by a simple chemical precipitation method were thoroughly characterized. The morphological, structural, compositional, photocatalytical, and biological properties of the prepared composites were investigated in comparison with those of the pristine components and correlated with the CdS concentration. ZnO−CdS composites contain flower-like structures, their size being tuned by the CdS amount added during the chemical synthesis. The photocatalytic activity of the composites was analyzed under UV irradiation using powders impregnated with methylene blue; the tests confirming that the presence of CdS along the ZnO in composites can improve the dye discoloration. The biological properties such as antioxidant capacity, antibacterial activity, and cytotoxicity of the ZnO, CdS, and ZnO−CdS composites were evaluated. Thus, the obtained composites presented medium antioxidant effect, biocidal activity against Escherichia coli, and no toxicity (at concentrations less than 0.05 mg/mL for composites with a low CdS amount) for human fibroblast cells. Based on these results, such composites can be used as photocatalytic and/or biocidal additives for photoactive coatings, paints, or epoxy floors, which in their turn can provide a cleaner and healthier environment.